From elections to democracy : building accountable government in Hungary and Poland - Rose-Ackerman, Susan (Cambridge University Press, 2005)
This study documents the weaknesses of public oversight and participation in policymaking in Hungary and Poland. It discusses five alternative routes to accountability including European Union oversight, constitutional institutions such as presidents and courts, devolution to lower-level governments, the use of neo-corporatist bodies, and open-ended participation rights.